Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004407.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for measles, mumps and rubella in children

Abstract: The design and reporting of safety outcomes in MMR vaccine studies, both pre- and post-marketing, are largely inadequate. The evidence of adverse events following immunisation with MMR cannot be separated from its role in preventing the target diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 101 publications
1
41
0
5
Order By: Relevance
“…Furthermore, developmental delay, admission to NICU for long period, day care attendance, past history of FC, deficiency in iron and zinc level and possibly some immunization such as (DPT and MMR) can be a risk factor for febrile convulsion. [7] In addition, a genetic cause for FC has been suggested, but still no susceptible gene has been identified. Febrile convulsion may occur before or soon after the onset of fever, with the likelihood of convulsion increasing with the child's temperature and not with the rate of temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, developmental delay, admission to NICU for long period, day care attendance, past history of FC, deficiency in iron and zinc level and possibly some immunization such as (DPT and MMR) can be a risk factor for febrile convulsion. [7] In addition, a genetic cause for FC has been suggested, but still no susceptible gene has been identified. Febrile convulsion may occur before or soon after the onset of fever, with the likelihood of convulsion increasing with the child's temperature and not with the rate of temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the 1990s, the link between the measles, mumps, and rubella (MMR) vaccines and autism, made on the basis of poor quality research coupled with self-serving and commercial interest, had a major and serious negative public impact. This impact instigated a very large number of new studies where the putative link was not found (Demicheli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The number of cases in 1994-1998 may therefore be an overestimation and the current increase even more marked. [11,12]. In addition, epidemiological studies have shown that the effectiveness declines with time since last vaccination [13,14] and antibody titers exhibit a gradual decline over time [15][16][17], implicating waning immunity as an underlying reason for the observed mumps resurgence.…”
Section: Discussionmentioning
confidence: 99%